Analyzing the Impact of IMF Policies on the Economic Health of the Pakistan - Bozdar, Imran Khan; Hussain, Nazar; Lashari, Irfan Ali; Lashari, Ali Raza; Shah, Abdullah (iRASD Journal of Economics, 2023)
The International Monetary Fund is called a lender of a last resort for those countries who are in need of emergency bail outs. Countries faced bankruptcies as they exhausted all of their options hence the option left for them is to approach the IMF. The International Monetary Fund was originally founded on the idea of helping countries who were to finance their debts. This would have provided stability in the financial market, improve growth and reduce poverty. The objective of this study was to analyze the impact of IMF policies on the economic health of the Pakistan. The results suggest that IMF programs have increased external debt to GDP ratio, which in return increased debt burden on the economy. IMF policies led to increase in taxes, which induce inflation and lower growth. The results further concluded that structural adjustment programs affected negatively to the domestic economy. Due to IMF, economy has to achieve stabilization, which leads decline in growth. The decline in fiscal deficits through increase in taxes and reduction in development expenditure led to increase in unemployment and social decline. The devaluation of the currency increases inflation in the economy whereas reduction subsidies increase costs in the rural economy. As most of the agricultural inputs required subsidies so they are mostly effected by reduction in subsidies. The IMF program also increases pressure on external debt, which leads to acquiring of further debt in order to pay the previous debt. This accumulation of debt increases external debt to GDP ratio and increases the sovereign risk of a country. To come out of vicious cycle perpetuated by IMF prescription, Pakistan needs alternate solutions including overhaul of its export policy to boost export; aggressive privatization to curtail expenditure; floating of international bonds to build up foreign exchange reserves and invest agriculture, livestock and dairy sectors for inclusive growth.